Productos y subproductos obtenidos de la yuca (Manihot esculenta Crantz) - Toledo Zumaeta, Elda Adela (2022)
This research work has the purpose of explaining how cassava (Manihot esculenta Crantz), also called Manioc, how the crop is managed, the different varieties of this tuber, how it is planted, how the different pests are combated, growth time and cassava harvest, likewise show the different varieties approximately 38, which is grown in Loreto, specifically in Ucayali, (Jenaro Herrera), their yields per hectare, yield in flour, starch, and the nutritional composition of various sources is also shown research, (Ministry of Health, since 1976, 2009, 2012, 2017), of the raw material such as cassava (Manihot esculenta Crantz). Subsequently, the process flows of various products were carried out, such as: process flows for obtaining flour, fariña, starch, making bread and crackers, having cassava as raw material, with their respective formulation of each of the products and their respective parameters in each step of the process, as well as their respective figures for each product. Subsequently, the nutritional composition of different types of cassava flour (as substitute flour) was shown, comparing it with respect to wheat flour, where the difference in components such as fat, protein and energy content is observed, where this difference is observed, Later, its sustainability as an alternative crop to replace wheat flour and its use in products above (flour, fariña, starch, bread, biscuits) were also discussed.